The influence of sim service quality, visitor facilities and police performance on sim service user satisfaction at the Serang Regency Police - Zainudin, Ahmad; Sukhaerah, Erah; Mutmainah, Mutmainah; Sumarjo, Wahid; Tajudin, Tajudin (Enrichment : Journal of Management, 2026)
This study looks at how service quality and visitor facilities affect police performance and user satisfaction among staff at the Serang Regency Police Resort (Polres). It examines both individual and combined effects. The population included all 97 people at the Polres, and they were selected using a saturated sampling method. For hypothesis 1, the results showed that the calculated t-value (7.117) was higher than the critical t-value (1.985), with a significance level of 0.00, which is less than 0.05. This means service quality has a significant impact on the performance of the Indonesian National Police. For hypothesis 2, the t-value (6.120) was also higher than the critical t-value (1.985), with a significance level of 0.00, indicating that visitor facilities significantly affect police performance. Hypothesis 3 showed a t-value of 2.534, which is above 1.985, with a significance level of 0.01, meaning police performance significantly influences user satisfaction. Finally, hypothesis 4 had an F-value of 29.942, which is greater than the critical F-value of 3.093, with a significance level of 0.00, showing that both service quality and visitor facilities together have a significant effect on police performance at the Serang Regency Police Resort (Polres).